Enhancing Student Moral Development Through Character Education Management Based on Religious Culture in Special Education Schools: A Case Study in Cirebon, Indonesia - Sarip, Hasan; Munajim, Ahmad; Sukarnoto, Toto; Asro’i, Asro’i; Sugiyatno, Agus; Nasikhin, Moch Mahdiyan (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study aims to address the moral decline among students in the context of globalization by exploring the concept of character education management based on religious culture in special education schools in Cirebon, Indonesia. The focus is on understanding how religious culture can enhance the quality of graduates and provide a solution to the moral challenges faced by the younger generation. Design/methods/approach – A qualitative case study design was employed to investigate the character education management at SLB Bina Mandiri, a special education school in Cirebon. Data were collected through in-depth interviews, participatory observations, and document analysis involving teachers, principals, and students. Thematic analysis was used to categorize and interpret the data, ensuring validity through triangulation and expert reviews Findings – The study found that effective character education management based on religious culture involves strategic planning, clear organizational roles, consistent implementation, and thorough supervision. Programs such as daily Quran recitation, congregational prayers, and religious observances foster a positive school environment and significantly enhance student discipline, respect, and religious understanding. These initiatives have led to the development of students with strong moral characters and high-quality graduates. Research implications – The findings suggest that other special education schools can adopt this model to improve their character education programs. The study highlights the importance of the principal's role in planning and organizing religious programs to ensure consistency and commitment from all school components. Future research should explore the long-term impacts and applicability of this management model in different educational contexts.